Mechanical Properties and Failure Analysis of 3D-Woven Copper Wire/Glass Fiber Hybrid Composites. Issue 5 (September 2020) - Xu, Fujun; Zheng, Liangang; Zhang, Kun; Aouraghe, Mohamed Amine; Saleemi, Sidra; Cao, Yanhong; Qiu, Yiping
Three-dimensional woven fabrics with excellent structural integrity are a very promising structure for multifunctional materials hybridized with various yarns. To systematically investigate mechanical properties and failure analysis of 3D-woven hybrid composites, copper wire/glass fiber composites with two hybrid structures, single-face copper wire (SF-CW) and double-face copper wire (DF-CW), were fabricated and tested. The SF-CW hybrid composites showed excellent tensile strength (1214 MPa) and bending strength (964 MP), which was greater than that of the DF-CW hybrid composites. Additionally, the compression strength and impact resistance of both composites exhibited comparable properties with traditional materials. Furthermore, all failure cross sections showed superior structural integrity and anti-delaminate properties, demonstrating that 3D-woven composites can be a good candidate platform by hybridization with various multifunctional yarns.